Mothering as a predictor on filial piety among Malaysian adolescents - Sarvarubini Nainee,; Tan, Soon Aun; Tan, Chee Seng (Penerbit Universiti Kebangsaan Malaysia, 2021)
Filial piety is an important value based on Confucian philosophy that emphasizes the virtue of respect towards parents and elderlies. As a priceless virtue, the tradition of filial piety has been adopted by many people regardless of the beliefs and ethnicity. Parents particularly mothers’ play an important role in sowing filial piety to their offspring. Mothers’ involvement in the upbringing of their children influences the degree of filial piety the children have towards elderlies. In line with that, this study explored the influence of mothering dimensions (involvement, rejection, structure, chaos, autonomy support, and coercion) on reciprocal and authoritarian filial piety among Malaysian adolescents. This study involved 594 secondary school students aged between 13 to 17 years old, selected by using cluster sampling method from three states of Peninsular Malaysia. A quantitative method with a self-administrated questionnaire was used to collect the data of the study. Pearson correlation analysis was performed and the findings of the study specified that all mothering dimensions significantly correlated with reciprocal filial piety. Conversely, only three mothering dimensions were associated with authoritarian filial piety. Multiple regression analyses were conducted to examine the influence of mothering on reciprocal and authoritarian filial piety. Findings indicated that involvement and autonomy support predicted reciprocal filial piety. Moreover, involvement was found to have a significant impact on authoritarian filial piety. This study suggests that mothers’ care and involvement are vital in enhancing filial piety among youngsters.